Emulsifying Properties of Sesame Seed Protein Hydrolyzates - Sreedevi, S.; Sivasankar, B. (Asian Journal of Chemistry, 2010)
Sesame seed protein isolates have been hydrolyzed using enzyme trysin and mixed proteases. The degree of hydrolysis (6, 8 and 10 %) was determined by the pH-stat method. The emulsifying activity, emulsion stability, effect of time and temperature on emulsio stability were determined. The effect of pH and degree of hydrolysis on the emulsification properties were also studied.